The Rise and Fall of Algal Blooms – Systemic Aversion from Limits to Growth, I - Dikou, Angela (Global Journal Of Botanical Science, 2019)
Rising trends in contemporary local ubiquitous algal blooms worldwide are positively associated with historic unprecedented rates of C, N, and P accumulations in waters and sediments in all types of aquatic ecosystems. A synthesis of patterns, processes, and mechanisms of algal blooms from different spatial and temporal scales reveals that they are a symptom of systemic changes in the intensity of the trophic and the detrital food webs scaffolded through the interaction of warming, fertilization and over fishing. Research with reference sites within protected areas; on ecological stoichiometry; and on socio-ecological systems are recommended in forecasting, monitoring, and policy regarding algal blooms to timely avert from limits to growth without unintended consequences.